2021
DOI: 10.1111/all.14749
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of house dust mite sensitization profiles in allergic adults from Canada, Europe, South Africa and USA

Abstract: Background Sensitization to house dust mite (HDM) is a leading cause of allergic rhinitis and asthma. Despite more than 30 HDM‐derived allergens having been identified to date, specific therapeutic approaches do not yet take into account the local sensitization profiles of patients. This study aimed to identify patterns of HDM sensitization in HDM‐allergic adults living in distinct geographic areas, to inform the development of targeted diagnostic and therapeutic tools. Methods Serum samples from 685 HDM‐aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 54 publications
6
59
4
Order By: Relevance
“…Two recent studies provided evidence that HDM allergen extract-based AIT vaccines provide mainly protection against Der p 1 and Der p 2 whereas they induce low or no IgG antibody responses to Der p 5, Der p 7, Der p 21, and Der p 23, and treatment success is lower in patients who are sensitized against the latter allergens as compared to patients who are mainly sensitized to Der p 1 and/or Der p 2 ( 17 , 18 ). Der p 7 has been defined as a mid-tier house dust mite allergen recognized by more than 30% of HDM sensitized patients ( 3 ) but it has been shown that it can be a major HDM allergen recognized by more than 50% of HDM allergic patients in certain populations ( 5 , 9 ). However, not only the frequency of IgE recognition defines if an allergen is important but also its clinical relevance which may be measured by determining its allergenic activity in vitro and in vivo needs to be taken into consideration as has been suggested recently ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies provided evidence that HDM allergen extract-based AIT vaccines provide mainly protection against Der p 1 and Der p 2 whereas they induce low or no IgG antibody responses to Der p 5, Der p 7, Der p 21, and Der p 23, and treatment success is lower in patients who are sensitized against the latter allergens as compared to patients who are mainly sensitized to Der p 1 and/or Der p 2 ( 17 , 18 ). Der p 7 has been defined as a mid-tier house dust mite allergen recognized by more than 30% of HDM sensitized patients ( 3 ) but it has been shown that it can be a major HDM allergen recognized by more than 50% of HDM allergic patients in certain populations ( 5 , 9 ). However, not only the frequency of IgE recognition defines if an allergen is important but also its clinical relevance which may be measured by determining its allergenic activity in vitro and in vivo needs to be taken into consideration as has been suggested recently ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, Der p 7 was categorized as mid-tier group of mite allergens with a frequency of IgE binding 17% to 52% depending on the tested population ( 4 8 ). A very recent study reported an IgE prevalence of 56% for Der p 7 in a South African population, and accordingly, Der p 7 was the second most common sensitizing allergen after Der p 23 in this population ( 9 ). The clinical relevance of Der p 7 was emphasized already in the study by Lynch et al.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that the capacity of Der p 23 to exacerbate mite allergic symptoms is very high, and this does not correlate with its abundance 1–3,5 . However, its sensitisation has been related to asthma, mainly in children 4 .…”
Section: Figurementioning
confidence: 98%
“…In recent years, Der p 23, a peritrophin‐like protein that is mainly present in the posterior midgut and the outer membrane of mite faeces, has also been identified as a potent allergen, despite its low concentrations 1,2 . Previous studies have demonstrated that Der p 23 elicits a positive sensitisation rate of 75% in patients with house dust mite (HDM) allergies, particularly in children with persistent moderate‐to‐severe asthma 2–5 . Different studies have investigated the correlation between the levels of HDM allergen exposure and risk of developing allergic sensitisation and, consequently, allergic symptoms 3,6 .…”
Section: Figurementioning
confidence: 99%